ANALISIS FAKTOR PENYEBAB KEMUNGKINAN KORUPSI DI KALANGAN APARATUR SIPIL NEGARA (ASN) : PERSPEKTIF GONE THEORY - Adinda Rachmania Prabandari; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
Corruption within local bureaucracies remains a significant challenge in Indonesia’s public governance. This study aims to analyze the potential risk of corruptive behavior among Civil Servants (Aparatur Sipil Negara/ASN) in the Bekasi City Government based on the GONE Theory framework (Greed, Opportunity, Need, and Exposes). The research employs a descriptive quantitative approach through a survey of 86 civil servants and is analyzed using descriptive statistics and cross-tabulation based on position levels. The findings indicate that Greed and Opportunity fall within the moderate category, while Need and Exposes vary across organizational positions. The relatively high perception of Exposes suggests uneven effectiveness in supervision and misconduct disclosure mechanisms within the organization. The principal finding of this study confirms that the potential risk of corruption in the bureaucracy is not determined solely by individual morality, but rather emerges from the interaction between internal motivations of civil servants and the structural opportunities available within the organization. Therefore, corruption prevention strategies should not rely exclusively on regulatory enforcement, but must also strengthen internal oversight systems and institutional integrity.